2014
DOI: 10.1556/crc.42.2014.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two wheat doubled haploid populations for resistance to common bunt and its association with agronomic traits

Abstract: Two segregating populations of doubled haploid (DH) wheat lines derived androgenetically from crosses 'Svilena' (susceptible) × A-38b-4-5-3-3 (highly resistant) and 'Svilena' × WWRN (moderately resistant to moderately susceptible) were characterized for resistance to common bunt. Disease incidence was evaluated after inoculation of seeds with a mixture of Tilletia foetida teliospores in two autumn sown field experiments. Two-gene model of inheritance of resistance in line A-38b-4-5-3-3 was suggested. The trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…They did not find any correlation between plant height and number of days to heading in one population consisting of 48 lines, while a low significant correlation was found between the resistance and days to heading (0.23*) and plant height (0.24**) in the other population with 115 genotypes. Based on our results and the results of [ 22 ] we can conclude that common bunt resistance seems to be an independent trait. The negative correlation between the percentage of infected heads and days to heading indicated that susceptible genotypes are usually heading earlier than resistant genotypes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…They did not find any correlation between plant height and number of days to heading in one population consisting of 48 lines, while a low significant correlation was found between the resistance and days to heading (0.23*) and plant height (0.24**) in the other population with 115 genotypes. Based on our results and the results of [ 22 ] we can conclude that common bunt resistance seems to be an independent trait. The negative correlation between the percentage of infected heads and days to heading indicated that susceptible genotypes are usually heading earlier than resistant genotypes.…”
Section: Discussionsupporting
confidence: 76%
“…No significant correlation was found between common bunt resistance and plant height. The correlation between common bunt resistance and agronomic traits was previously tested in two different doubled haploid population [ 22 ]. They did not find any correlation between plant height and number of days to heading in one population consisting of 48 lines, while a low significant correlation was found between the resistance and days to heading (0.23*) and plant height (0.24**) in the other population with 115 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide set of the common bunt differential lines is very useful in identifying common bunt resistance genes in the germplasm of the tested genotypes. Using the differential lines for that purpose was performed previously [ 38 , 39 , 40 , 41 ]. These differential lines are available in the Department of Agricultural Research Service, National Small Grains Collection (NSGC) in Aberdeen, ID, and could be easily separated from each other, which makes them globally important [ 40 ].…”
Section: Discussionmentioning
confidence: 99%